Pemanfaatan Teknologi Sebagai Sumber Informasi Pendampingan Terhadap Anak - Mariah Mariah; Dewi Nurbaiti (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
This activity is an implementation of the Tri Dharma of Higher Education at the Kalbis Institute in 2019. Community Service (PKM) is carried out in the form of training in the field of entrepreneurship and structured marketing concepts, and also on awareness training on technological progress and shifting in the Industrial Revolution era 4.0. This training is intended for all people to be able to adapt to lifestyle changes that occur and utilize technology as a source of assistance to children as the forerunner to the successor of family businesses. The implementation of PKM activities went smoothly, the benefits obtained by the PKK RW 09 mothers after attending the training are: (1) Matraman PKK group is motivated to use technology as a source of assistance to children; (2) the PKK group is able to carry out external and internal analysis both of themselves and their families; (3) the PKK group is able to apply the concept of digital children's modern accompaniment; and (5) the PKK group is able to monitor, evaluate and create solutions in assisting their children. Keywords: technology utilization, digital based learning